2012
DOI: 10.3390/molecules17066754
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long-Term Effects of Baccharis articulata on Glucose Homeostasis

Abstract: In this study, the in vivo effect of the crude extract and n-butanol and aqueous residual fractions of Baccharis articulata (Lam.) Pers. on serum glucose levels, insulin secretion and liver and muscle glycogen content, as well as in vitro action on serum intestinal disaccharidase activity and albumin glycation were investigated. Oral administration of the extract and fractions reduced glycemia in hyperglycemic rats. Additionally, the n-butanol fraction, which has high flavonoids content, stimulated insulin sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Antimicrobial, antioxidant (Benli et al 2007;Lopes-Lutz et al 2008), hepatoprotective, anti-inflammatory (Obolskiy et al 2011), hypoglycemic (Ribnicky et al 2006), antiplatelet (Tognolini et al 2006), anticonvulsant (Sayyah et al 2004). Antitumor (Abdelhamed et al 2013), antimicrobial (Poiată et al 2009), antiviral (Meneses et al 2009), antispasmodic, bronchodilatory (Khan and Gilani 2009), antioxidant (Temraz and El-Tantawy 2008), antiinflammatory (Tigno and Gumila 2000), analgesic (Pires et al 2009 Antioxidant (Verdi et al 2005), antimicrobial (Simoniato et al 2008), antiviral (Torres et al 2011), antiinflammatory (Gené et al 1992), hypoglycemic (Kappel et al 2012). Antioxidant, antimicrobial (Verdi et al 2005), antiviral (Mangiaterra 2005), anti-inflammatory (Gené et al 1992 Anti-inflammatory (Gonzales Dávalos et al 2007), antimicrobial (Verástegui et al 1996), anthelmintic (Salazar et al 2007 Antioxidant (Pádua et al 2010), hepatoprotective, antimutagenic (Verdi et al, 2005), hypoglycemic , antiparasitic (Gianello et al 2000), immunomodulatory (Paul et al 2009), antimicrobial, antiviral (Mangiaterra 2005), analgesic, antiinflammatory (Gené et al 1992, 1996), vasodilatory (Hnatyszyn et al 2003 Antitumor (Matić et al 2012;Wegiera et al 2012), antimicrobial (Szakiel et al 2008), antiviral (HIV)...…”
Section: Species/productsmentioning
confidence: 99%
“…Antimicrobial, antioxidant (Benli et al 2007;Lopes-Lutz et al 2008), hepatoprotective, anti-inflammatory (Obolskiy et al 2011), hypoglycemic (Ribnicky et al 2006), antiplatelet (Tognolini et al 2006), anticonvulsant (Sayyah et al 2004). Antitumor (Abdelhamed et al 2013), antimicrobial (Poiată et al 2009), antiviral (Meneses et al 2009), antispasmodic, bronchodilatory (Khan and Gilani 2009), antioxidant (Temraz and El-Tantawy 2008), antiinflammatory (Tigno and Gumila 2000), analgesic (Pires et al 2009 Antioxidant (Verdi et al 2005), antimicrobial (Simoniato et al 2008), antiviral (Torres et al 2011), antiinflammatory (Gené et al 1992), hypoglycemic (Kappel et al 2012). Antioxidant, antimicrobial (Verdi et al 2005), antiviral (Mangiaterra 2005), anti-inflammatory (Gené et al 1992 Anti-inflammatory (Gonzales Dávalos et al 2007), antimicrobial (Verástegui et al 1996), anthelmintic (Salazar et al 2007 Antioxidant (Pádua et al 2010), hepatoprotective, antimutagenic (Verdi et al, 2005), hypoglycemic , antiparasitic (Gianello et al 2000), immunomodulatory (Paul et al 2009), antimicrobial, antiviral (Mangiaterra 2005), analgesic, antiinflammatory (Gené et al 1992, 1996), vasodilatory (Hnatyszyn et al 2003 Antitumor (Matić et al 2012;Wegiera et al 2012), antimicrobial (Szakiel et al 2008), antiviral (HIV)...…”
Section: Species/productsmentioning
confidence: 99%
“…However, previous investigations revealed that neuritogenic agent is limited to use because that NGF cannot pass through the blood-brain barrier due to its large molecular size and hydrophilic [5]. Gentiside is a kind of new neuritogenic activity compounds (shown in Figure 1) isolated from G. rigescens , which was researched to enhance the activity of endogenous neurotrophic factors and exhibited neurite elongation in PC 12 cells and gentisides' bioactivity was related to only alkyl chain length, not structural diversity of end of the alkyl chain [68]. Chemical structures of gentisides (A, B, G, H, I, J, and K) had been concluded in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Any increase in absorbance due to the spontaneous hydrolysis of substrate or unspecific enzyme inhibition was corrected by subtracting the absorbances between the samples and the blank incubation. The IC50 values were estimated by nonlinear regression analysis [1]. …”
Section: Determination Of α-Amylase Inhibitory Activitymentioning
confidence: 99%
“…According to estimates by the World Health Organization (WHO), 80% of the population in developing countries use medicinal plants for basic health care and 85% of traditional medicine involves the use of plant extracts [4]. [1] argue that medicinal plants are particularly interesting because they can not only be used as complementary and alternative remedies to prevent metabolic diseases, but are also a source of compounds with the potential to originate new antidiabetic drugs. They are capable of controlling glucose homeostasis in Diabetic subjects, meaning a lot for the patient's health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation